Research on the level of processing hypothesis expanded to auditory awareness - Tanskanen, Sampo (My University, 2023)
According to the level of processing hypothesis (LoP), the transition from unaware to aware perception of low-level stimuli properties (energy, features) are graded, and high-level stimuli properties (semantic, words) is dichotomous. The LoP has been proposed as an explanation for different results in behavioral studies stemming from two competing theories of consciousness, the recurrent processing theory (RPT) and the global neuronal workspace theory (GNWT). RPT proponents have found that level of awareness increases gradually, whereas GNWT proponents have observed the level of awareness increasing dichotomously, in an all-or-none fashion. Previously, the LoP hypothesis has been tested solely in the visual modality and majority of the research has relied only on the behavioral data. In this thesis, we aimed to expand the research from the visual modality to the auditory modality to test the LoP hypothesis using both behavioral and electrophysiological responses. We investigated whether different levels of processing can be observed in both behavior and electrophysiological responses in auditory modality. To achieve this, we collected the EEG signals from participants while they listened to the near-threshold auditory stimuli and responded using both a perceptual awareness scale (PAS) and a forced-choice behavioral task. Our behavioral results supported the LoP hypothesis by revealing a linear correlation in the lowerlevel task between the perceptual awareness scale and accuracy, as well as the percentage of used trials. The same pattern emerged in the higher-level task, with the exception that it showed less linearity, suggesting that higher-level processes are not entirely dichotomous as the LoP postulates. Regarding our electrophysiological results, we observed auditory awareness negativity (AAN) and late positivity (LP), but only the LP time window was found to correlate with PAS rating. As there is controversial evidence that the more negative activation was associated with higher PAS rating, this could be a prolonged AAN. We propose two reasons for this observation. AAN was not associated with the PAS rating in both tasks probably due to the 1) small sample size and weak sound stimulation 2) or because AAN is prolonged, it is observed in the LP time window. To our knowledge, the study we devised is the first to test the LoP on auditory awareness, and we successfully expanded the LoP testing paradigm from the visual modality to the auditory modality based on the behavior results. Considering our behavioral results and the limitations with the sample, the electrophysiological data have the potential to support the LoP as well.
Keywords: Consciousness, phenomenal consciousness, access consciousness, levels of processing, auditory awareness negativity, perceptual awareness negativity, late positivity, event-related potential, electroencephalogram